Transmitter selection and receiver placement for target parameter estimation in cooperative radar‐communications system - Liming Wang; Qian He; Huiyong Li (IET Signal Processing)
Abstract Target parameter estimation is considered for the cooperative multiple‐input multiple‐output (MIMO) radar and MIMO communications system. To address the hardware limitation of the radar system, a joint transmitter selection and receiver placement (JTSRP) problem is formulated to minimise the estimation performance benchmarked by the Cramer–Rao bound (CRB), where the transmitters can be selected from a discrete set and the receivers can be deployed over a continuous region. To efficiently solve this mix‐integer non‐linear programming problem approximately, a genetic algorithm (GA)‐based method is proposed. It is shown that the result obtained by the proposed algorithm is close enough to the optimum solution of the JTSRP problem. Numerical examples are presented to analyse the performance of the cooperative system designed by the GA‐based JTSRP.